Mesoscale Thermal Conductivity and Resistivity of Polycrystalline Graphite - Jawad, Sayed Husain (2015)
A Master of Science thesis in Mechanical Engineering by Sayed Husain Jawad entitled, "Mesoscale Conductivities and Resistivities of Polycrystalline Graphite," submitted in July 2015. Thesis advisor is Dr. Mohamed Gadalla and thesis co-advisor Dr. Shivakumar I. Ranganathan. Soft and hard copy available.